Characterisation of hyper tolerant Bacillus firmus L-148 for arsenic oxidation. (June 2020) - Bagade, Aditi; Nandre, Vinod; Paul, Dhiraj; Patil, Yugendra; Sharma, Nisha; Giri, Ashok; Kodam, Kisan
Abstract: Groundwater arsenic pollution causes millions of deaths worldwide. Long term natural and anthropogenic activities have increased arsenic levels in groundwater causing higher threats of arsenic exposure. Arsenic hyper-tolerant Firmicute Bacillus firmus L-148 was isolated from arsenic limiting Lonar lake soil, which tolerated more than 3 M arsenic and could oxidize 75 mM arsenite [As(III)] in 14 days. It oxidized As(III) in presence of heavy metals and had unusual pH optima at 9.2. B. firmus L-148 was studied at the biochemical, protein, genomic and transcript level for understanding its arsenic oxidizing machinery. The proteomic and transcript analysis exhibited the presence of ars and aio operon and supported the inducible nature of ars operon. Robust, hyper-tolerant, fast As(III) oxidizing, least nutrient requiring and multi-metal resistance qualities of the strain were used in microcosm studies for bioremediation. Artificial groundwater mimicking microcosm with 75 mM As(III) was developed. Modulation of carbon source, iron and multi metals affected growth and As(III) oxidation rate. The As(III) oxidation was recorded to be 77% in 15 days in presence of sodium acetate and Fe ions. This microcosm study can be explored for bioremediation of arsenic contaminated water and followed by precipitation using other methods. Graphical abstract: Image 1 Highlights: Hypertolerant arsenic oxidizing bacteria isolated from arsenic trivial Lonar Lake. Multi metal tolerance property useful in groundwater remediation. Infrequent pH 9.0 optimum for arsenite oxidation reported. Microcosm studies relate to arsenic bioremediation of contaminated groundwater. Abstract : Bacillus firmus L-148 with extremely high tolerance towards arsenic was used for remediation of contaminated water at microcosm scale.